Stress and quality of working life : finding meaning in grief and suffering - Rossi, Ana Maria; Meurs, James A.; Perrewé, Pamela L. (Stress and quality of working life., 2020)
"This book is designed to be an additional tool to provide information and to suggest ways to deal with pressures and work demands, because stress levels are still on the rise. We believe that through information - and here you will be able to find the experience and opinions of recognized professionals in this area - workers will be able to live better and more balanced lives. According to the American Institute of Stress (AIS), job stress is far and away the primary source of stress for American adults. The relationship between job stress and heart attacks, hypertension, and other disorders is well understood. Further, the cost of job stress in the United States is estimated to be over $300 billion due to outcomes such as accidents, turnover, and lost productivity. Perhaps the most consistent findings connecting job stress to health outcomes confirm that employees who perceive a high level of job demands without the appropriate control over job demands are at an increased risk for cardiovascular disease. In Brazil, the loss is estimated at 3.5% of the Gross Domestic Product per year. Occupational diseases are related to the activities performed by workers and to working conditions and can trigger new or worsen already existing symptoms. Proper diagnosis and relevant information are essential for managers and workers to become aware of stressors and to take efficient measures to manage stress. Although quality of life is the responsibility of every individual, companies will definitely be able to benefit from the implementation of preventive actions, thus avoiding to pay a high price as a result of absenteeism, sick leaves, and drops in productivity and low work quality"--